Environmental Health Inspection of Sanitation Facilities at the Religious Tourism Tomb of Syaikhona Kholil Bangkalan, East Java - Ilmiyatul Asroriyah; Rachmaniyah; Putri Arida Ipmawati; khambali; Iva Rustanti; Estim, Abentin; Anwar, Taufik (Jurnal Higiene Sanitasi, 2025)
Religious tourism is one of the fastest-growing tourism sectors in Indonesia. However, the increasing number of visitors each year, combined with inadequate maintenance of sanitation facilities at religious sites, may elevate the risk of disease transmission. This study aimed to evaluate the condition of sanitation facilities at the Syaikhona Kholil Religious Tourism Site in Bangkalan. A descriptive survey design was employed to assess several key sanitation indicators, including the provision of clean water, wastewater disposal, waste management, toilet facilities, healthcare facilities, fire extinguishing equipment, and educational signage. The findings indicated that the overall sanitation facility score was categorized as "moderate" (63%). Specifically, waste management (75%) and toilet facilities (77%) were rated as moderate, while healthcare facilities (20%) and fire extinguishers (20%) were deemed inadequate. Educational signage achieved a moderate score (50%). The study concludes that several sanitation components at the site fail to meet required standards. Improvements in facility maintenance, waste management, healthcare provision, fire safety measures, and public health education are recommended to enhance sanitation standards, promote visitor safety, and reduce the risk of disease transmission.